Survival of Atlantic salmon and sea trout smolts in transitional waters - Artero, Celine; Gregory, Stephen; Beaumont, William A.; Josset, Quentin; Jeannot, Nicolas; Cole, Alan; Lamireau, Ludivine; Réveillac, Elodie; Lauridsen, Rasmus B. (Marine Ecology Progress Series, 2023)
International audience Monitoring the first seaward migration of juvenile salmonids, known as smolts, is challenging because there is limited tracking technology suited to their small size. Nevertheless, for their management and conservation purpose, it is critical to understand this phase of their life cycle when they adapt to increased salinity, novel predators and new prey. Smolts of 2 species, Atlantic salmon Salmo salar and brown trout Salmo trutta , were acoustically monitored at 4 study sites, together with biotic and abiotic parameters, to estimate and explain their survival during their estuarine migration to sea. The 2 species exhibited different levels of survival during this seaward migration, with a higher survival for trout smolts. For both species, survival was similar among 3 of the 4 sites. Migration speed and migratory distance influenced smolt estuarine survival, but body length, body condition, sex, age, and environmental parameters (temperature, salinity, dissolved oxygen) did not. Migration speed, potentially reflecting smolts’ capacity to avoid predators or escape dangerous areas, had a positive effect on their survival. Increased distance negatively influenced estuarine survival, which could lead to lower survival rate in the River Frome Estuary where orientation is more difficult for smolts due to widely separated environmental cues. Overall, smolt survival through estuaries was estimated between 51 and 97% among 4 populations, suggesting that estuaries are variably challenging environments for migrating smolts, accounting for non-negligible early marine survival. Understanding which estuaries have low survival and why is imperative to prioritise management actions.